Sustainable Construction Project Management: Developing a Framework for Assessing Sustainability Performance in Nigerian Mega Projects - Unegbu, H C O; Yawas, Danjuma Saleh; Dan-asabe, Bashar; Alabi, A.A. (Civil and Environmental Science Journal (CIVENSE), 2025)
This study develops a tailored sustainability assessment framework for Nigerian mega projects. The framework is applied to four diverse case studies: a highway expansion, an airport terminal, a renewable energy project, and a residential housing development. Results show that the renewable energy project achieved the highest sustainability score due to its superior environmental and economic performance. In contrast, the highway expansion project ranked the lowest, primarily because of its significant environmental impact and limited community engagement. Key findings emphasize the critical role of community engagement and lifecycle costing in achieving sustainable outcomes. Projects that incorporated inclusive planning and long-term financial strategies performed better overall. However, the study also identifies significant barriers, including weak regulatory enforcement and monetary limitations, which restrict the adoption of sustainable construction practices. The research highlights the need for localized sustainability frameworks in developing countries, as international models like LEED and BREEAM may not fully address context-specific challenges. This framework provides a valuable tool for policymakers, project managers, and stakeholders to enhance sustainability in large-scale infrastructure projects and support long-term development objectives.